PENGARUH KOMUNIKASI INTERPERSONAL DAN BUDAYA KERJA TERHADAP KUALITAS KINERJA STAF UPTD PUSKESMAS II DINAS KESEHATAN KECAMATAN DENPASAR TIMUR - Putu Adi Narendra; I Dewa Ayu Hendrawathy Putri; I Gusti Ngurah Pertu Agung (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Numerous crucial viewpoints to comprehend the culture of company communication. It's critical that the front and back communicate with each other. Work culture plays a key role in launching corporate operations by improving human capital and human resource management (SDM) to boost productivity and reduce business risks over time. The ability of employees to work effectively and meet predetermined productivity targets in order to maximize their contributions is the basis for measuring worker productivity. The aim of this research is to investigate the effects of work culture and interpersonal communication on the employees of UPTD Puskesmas II Dinas Kesehatan Kecamatan Denpasar Timur. The quantitative method is used in this investigation. Multiple linear regression analysis is used in this strategy. For this investigation, 66 employees made up the sample. from the East Denpasar District Health Office's UPTD Puskesmas II. A significant value of f less than 0.05 indicates that the work culture and interpersonal communication have a significant impact on the quality of staff performance, according to the research.